2022
DOI: 10.2174/1871526522666220107125511
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Status of Famotidine in COVID-19 Patients: A Review

Abstract: The novel coronavirus, SARS-coV-2, which emerged in Wuhan in November 2019, has increasingly spread worldwide. More than 272 million cases of infection have been identified. COVID-19 affects 223 countries and territories across the world. The principal target of the SARS-CoV-2 infection is the lower respiratory tract. Series of moderate to non-specific severe clinical signs and symptoms that appear two to fourteen days after exposure to SARS-CoV-2 can occur in patients with COVID-19 disease. There is cough, br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The novel coronavirus SARS-coV-2, which emerged in Wuhan in November 2019, has increasingly spread causing a global pandemic that infected more than 494 million people, resulting in severe social and economic ramifications, and claimed more than 6,183,000 lives by April 6, 2022 [ 1 ]. Coronavirus disease 2019 (COVID-19), which is attributable to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has been the cause of global health threats [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The novel coronavirus SARS-coV-2, which emerged in Wuhan in November 2019, has increasingly spread causing a global pandemic that infected more than 494 million people, resulting in severe social and economic ramifications, and claimed more than 6,183,000 lives by April 6, 2022 [ 1 ]. Coronavirus disease 2019 (COVID-19), which is attributable to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has been the cause of global health threats [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The potential benefit of the H1 histamine receptor blocker Desloratadine is suggested by the measured decline in phospho-p38 and by inhibition of the SPRBD effects on expression of CHST15, CHST11 and ARSB, as well as by pharmacological studies that identified desloratadine/loratadine as a mechanism-based target [36][37][38]. Several clinical studies of H2 blockers on the response in Covid-19 have been reported and additional studies of antihistamines are ongoing [57][58][59].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism by which famotidine could improve the outcomes of COVID-19 is currently unknown. 39 It has been suggested that famotidine may reduce COVID-19 severity through antagonism or inverse agonism of histamine signaling. 40 A meta-analysis found no significant association between famotidine use and clinical outcomes.…”
Section: Overview Of Other Nutrientsmentioning
confidence: 99%